2020
DOI: 10.3390/cancers12020411
|View full text |Cite
|
Sign up to set email alerts
|

A Bispecific Inhibitor of the EGFR/ADAM17 Axis Decreases Cell Proliferation and Migration of EGFR-Dependent Cancer Cells

Abstract: Dysregulated epidermal growth factor receptor (EGFR) is an oncogenic driver of many human cancers, promoting aberrant cell proliferation, migration, and survival. Pharmacological targeting of EGFR is often challenged by acquired mechanisms of resistance. Ligand-dependent mechanisms in EGFR wild-type cells rely on ligand or receptor overexpression, allowing cells to outcompete inhibitors and perpetuate signaling in an autocrine manner. Importantly, EGFR ligands are synthesized as membrane-bound precursors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…They fused TDP with a competitive not-active EGFR-binding protein called DARPinE01. The resulting biomolecule had greater effects than non-engineered TPD on reducing migration and invasion of cancer cells [ 202 ].…”
Section: Strategies For Adam17 Inhibitionmentioning
confidence: 99%
“…They fused TDP with a competitive not-active EGFR-binding protein called DARPinE01. The resulting biomolecule had greater effects than non-engineered TPD on reducing migration and invasion of cancer cells [ 202 ].…”
Section: Strategies For Adam17 Inhibitionmentioning
confidence: 99%
“…Taking this into account, a recombinant prodomain peptide of ADAM17 was synthesized and shown to be an effective and highly specific inhibitor of ADAM17 activity in sepsis and inflammation models [199] and a murine kidney fibrosis model [200]. Recently, Soto-Gomez et al [201] have developed a bispecific fusion protein construct (E0-GS-TPD) consisting of the inhibitory prodomain peptide of ADAM17 fused to an EGFR-targeting design ankyrin repeat protein, which inhibits the proliferation of lung cancer cells [201]. The use of such specific proteins could be an innovative strategy for the treatment of EGFR-dependent cancers.…”
Section: Adam17/tacementioning
confidence: 99%
“…A disintegrin and metalloprotease metallopeptidase domain 17 (ADAM17) is a protease for epidermal growth factor receptor (EGF-R) ligand processing [ 80 ]. It has been recently shown that ADAM17 can accelerate the tumorigenesis of CRC [ 81 ].…”
Section: The Role Of Malat1 In Colorectal Cancermentioning
confidence: 99%